Warraparna Kaurna! Reclaiming an Australian language - Amery, Rob (University of Adelaide Press, 2016)
This book tells the story of the renaissance of the Kaurna language, the language of Adelaide and the Adelaide Plains in South Australia, principally over the earliest period up until 2000, but with a summary and brief discussion of developments from 2000 until 2016. It chronicles and analyses the efforts of the Nunga community, and interested others, to reclaim and relearn a linguistic heritage on the basis of mid-nineteenth-century materials.